2018
DOI: 10.1111/nph.15506
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic role of the actin filament cytoskeleton

Abstract: This article is a Commentary on Zhang et al., 221: 1049–1059.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In soybean nodules, cytoskeletal arrays differ between uninfected and infected nodule cells and between developing and mature nodule cells ( 59 ). Continued reorganization of actin cytoskeleton is associated with rhizobium release from infection threads and symbiosome development ( 60 , 61 ). Notably, the key symbiotic phenotype associated with the inactivation of T3SS in incompatible Sinorhizobium strains is the shift from uninfected pseudonodules to well-infected nodules ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean nodules, cytoskeletal arrays differ between uninfected and infected nodule cells and between developing and mature nodule cells ( 59 ). Continued reorganization of actin cytoskeleton is associated with rhizobium release from infection threads and symbiosome development ( 60 , 61 ). Notably, the key symbiotic phenotype associated with the inactivation of T3SS in incompatible Sinorhizobium strains is the shift from uninfected pseudonodules to well-infected nodules ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides non-beneficial plant–pathogen interactions, MTs also function in beneficial symbiosis processes between plants and symbiotic microorganisms [ 205 ]. Active cytoskeletal rearrangements are required at different stages of nodule development, from root-hair curling for entrapment of rhizobia to infection thread growth [ 206 , 207 , 208 ]. Endoplasmic MTs appear to support infection thread growth, infection droplet formation, and bacterial release into the host cytoplasm in nodules of legume species, whereas irregular cortical MT arrangements provide a possibility for isodiametric cell growth that allows a notable increase in cell size for hosting numerous symbiosomes [ 209 ].…”
Section: Mts In Biotic Stress Responsesmentioning
confidence: 99%
“…It has been clearly demonstrated that active cytoskeleton rearrangements are required at different stages of nodule development ( Timmers, 2008 ; Genre and Timmers, 2019 ; Tsyganov et al, 2019 ). Symbiotic nodules can be subdivided into two main types: indeterminate and determinate ( Hirsch, 1992 ).…”
Section: Introductionmentioning
confidence: 99%